Praktik Public Relations (PR) di Indonesia (Masa Lalu, Masa Kini, dan Masa Datang) - Widodo Muktiyo (Jurnal Komunikasi, 2009)
This article tries tracing the development of Public Relations (PR) that has been emerging since the beginning of twentieth century in Uncle Sam country with Ivy Lee and Bemays as its main figures. At the nearly same time, Indonesia practiced many communication activities that could be categorized within PR terms such as building public opinion to enhance the importance of independence as a great value that must be fighter either nationally or internationally. PR practices in Indonesia are full of political nuances. Meanwhile, PR studies in US came up caused by economic recessions. Both different historical backgrounds have been bringing different implications in PR development until now days. PR practice in both independence and new order era was colorized by freedom and egalitarianism. Nevertheless, the fall of old order and the rise of new order or, then, the fall of new order and the rise of reformation order are not always on the same tracks. Its discontinuity is not favorable for democratic society atmosphere. Reformation order that is colorized by information and technology development increase PR practices in Indonesia, both quantitatively and qualitatively. Yet, the practice of PR in Indonesia is still dominated by political stakes and tent to less of business approach.